Influence of ball milling parameters on the mechano-chemical conversion of polyolefins - Hergesell, Adrian H; Seitzinger, Claire L; Burg, Justin; Baarslag, Renate J; Vollmer, Ina (RSC Mechanochemistry, 2025)
Ball-milling of addition polymers such as polyolefins, polystyrene and polyacrylates can be used for depolymerization to obtain the respective monomers. However, absolute yields are typically low, especially from polyolefins which are notoriously difficult to depolymerize. To increase the viability of ball milling as a recycling technique, the effect of milling parameters on small hydrocarbon and monomer yields has to be understood. Herein, we systematically investigate the influence of sphere material, milling frequency, plastic filling degree, and milling temperature. Heavy spheres and high milling frequencies boost hydrocarbon yields by maximizing mechanical forces and frequency of collisions. While the dose of kinetic energy is commonly used to describe mechano-chemical processes, we found that it does not capture the mechano-chemical depolymerization of polyolefins. Instead, we rationalized the results based on the Zhurkov equation, a model developed for the thermo-mechanical scission of polymers under stress. In addition, low plastic filling degrees allow for high percentage yields, but cause significant wear on the grinding tools, prohibiting sustained milling. Milling below 40 °C is beneficial for brittle chain cleavage and depolymerization. This study provides a new approach to rationalize the influence of individual milling parameters and their interplay and serves as a starting point to derive design principles for larger-scale mechano-chemical depolymerization processes. Mechano-chemical plastic recycling suffers from low overall yields. We identified the role of key parameters to maximize mechanical impact to increase the productivity of small hydrocarbons, such as propene, from polypropylene.